Said Writer to Reader. Translation as Lignification - Folkart, Barbara (TTR)

(untitled) (Association canadienne de traductologie, 1999)
AbstractSaid Writer to Reader. Translation as Lignification — Lignification, the degenerative process whereby language hardens into cliché and discourse remains stuck in the already-said, manifests itself in every type of language practise, from the everyday to the poetic.Translation, by its very nature, deals with the already-said, but the relationship is all too frequently regressive, at the level of both practise and theory : hence, the empirically observable inferiority of so many target-texts with respect to the sources they attempt to "replicate"; hence, too, the failure of so many theoretical models to have anything whatsoever to say about the actual production, in the target language, of texts that really are texts.This essay proposes, and illustrates, a writerly way of envisaging both the practise and the theory of poetic translation — an approach that emphasizes the writing of the target-text as opposed to the readerly-replicative models that give priority to analysis of the already-said.